2015
DOI: 10.1155/2015/310239
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy in Pregnancy: A Population-Based Study of Women with Pregestational Diabetes

Abstract: The aim of this observational study was to evaluate screening and progression of diabetic retinopathy during pregnancy in women with pregestational diabetes attending five antenatal centres along the Irish Atlantic seaboard. An adequate frequency of screening was defined as at least two retinal evaluations in separate trimesters. Progression was defined as at least one stage of deterioration of diabetic retinopathy and/or development of diabetic macular edema on at least one eye. Women with pregestational diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 20 publications
4
65
2
12
Order By: Relevance
“…32 Studies have confirmed that rapid optimization of glycaemic control after conception is a risk factor for progression of DR during pregnancy. 5,15,17,27,28,30 This is supported by the findings in the DCCT, where 53% of the conventional treatment group who were changed to intensive control in early pregnancy experienced worsening of DR during pregnancy comparedwith 40% in the initial intensive group. In this conventional treatment group, there was a significant rank correlation between initial higher HbA1c and a greater chance of DR progression, where 82% of those with a 3.1% or more decrease in HbA1c experienced progression of DR, 5 whereas improvements in HbA1c of up to 0.9% in a well-controlled cohort did not increase the risk of DR progression.…”
Section: Glycaemic Controlmentioning
confidence: 52%
See 2 more Smart Citations
“…32 Studies have confirmed that rapid optimization of glycaemic control after conception is a risk factor for progression of DR during pregnancy. 5,15,17,27,28,30 This is supported by the findings in the DCCT, where 53% of the conventional treatment group who were changed to intensive control in early pregnancy experienced worsening of DR during pregnancy comparedwith 40% in the initial intensive group. In this conventional treatment group, there was a significant rank correlation between initial higher HbA1c and a greater chance of DR progression, where 82% of those with a 3.1% or more decrease in HbA1c experienced progression of DR, 5 whereas improvements in HbA1c of up to 0.9% in a well-controlled cohort did not increase the risk of DR progression.…”
Section: Glycaemic Controlmentioning
confidence: 52%
“…Studies have consistently shown that the longer the duration of diabetes, the more likely retinopathy is to progress during pregnancy. [15][16][17]19,21,27,28 In T1DM, DR remained stable during pregnancy where the duration of diabetes was less than 10 years but progressed in 10% of those with a 10-to 19-year duration. 22 Another study found an average duration of 13.5 years in the group whose retinopathy remained stable, compared with 19.7 years duration in those with DR progression during pregnancy.…”
Section: Duration Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregestational diabetes is associated with an increased risk of adverse perinatal outcomes, including preeclampsia, 5, 6 retinopathy, 7 early fetal loss, 8, 9 stillbirth, 10 macrosomia, 11 birth injuries associated with large fetal size, and infant death. 10, 12 Given the burden of type 1 and type 2 diabetes during pregnancy, and recent changes in the racial-ethnic composition of women of reproductive age in the United States, understanding changes in the prevalence of pregestational diabetes, overall and by population subgroups, is important for informing health systems and clinicians of the resources required for the preconception and obstetric care of young women with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients should also be informed that an abrupt correction of metabolic balance in diabetes might lead to worsening of retinal changes [5,6].…”
Section: Ocular Examinationmentioning
confidence: 99%